PRAKTIK DAN MAKNA PERAYAAN SIWARATRI - I Ketut Wartayasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The practice of Hinduism in Bali is mostly sourced from literature. For example, the Siwaratri Celebration gets justification from the Siwaratrikalpa text. This text describes the journey of a hunter named Lubdaka to the forest to hunt. Until evening, none of the game animals were found, so he had to stay in the forest. In order to avoid wild animals, he also lived on a bilwa tree. In order to fight sleepiness, he plucked the bilwa leaves one by one and dropped them down and hit a phallus which was right under the tree. After his death, Lubdaka finally got to heaven because on that day he accidentally worshiped Shiva. This work descriptively tries to narrate the Siwaratri celebration along with its meaning. Lubdaka's story must be unraveled so that the spiritual value in it is visible and can be used as a guide. How Lubdaka as a hunter, does not get game, does not sleep all night, picks bilwa leaves, Shiva linga, and others must be contextualized with spiritual values. This celebration must also lead to people's spiritual awareness